Tax efforts and tax evasion–economic development Nexus. Does institutional quality matter? - John Kwaku Amoh; Kenneth Ofori-Boateng; Randolph Nsor-Ambala; Ebenezer Bugri Anarfo (Cogent Economics & Finance, 2023)
As a result of the failure to meet tax collection targets, policymakers, economists, and financiers have focused their attention in recent years on how a country's tax effort has been employed to combat tax evasion and maximise tax collections for economic growth. The study looked at the nexus between tax efforts, tax evasion, and economic development, as well as the effect of institutional quality on moderating the nexus in Ghana. The maximum likelihood (ML) estimation and structural equation modelling (SEM) techniques were used in the study to analyse a sample of quartered data from 1996 to 2020. Testing the hypotheses reveals that both tax efforts and tax evasion have negative effects on the economic freedom of the world index (EFWI) but positive effects on urbanisation. A test of the third hypothesis shows that institutional quality moderates tax evasion in Ghana in order to influence economic development. The findings imply that the idea that tax evasion is bad for an economy or that tax efforts drive domestic revenue mobilisation is based mainly on prima facie evidence. Tax efforts such as tax amnesty may appear to compliant taxpayers as an incentive for tax evaders, which could affect their compliance. The adoption of the tax efforts index measure to examine its econometric impact on economic development is one of the pioneering attempts in the field. The study recommends well-thought-out strategies to ensure that tax efforts achieve their intended goals.
Keywords: 330; economic development; Ghana; institutional quality; tax efforts; tax evasion